Perceptions of Novice Learners toward the Use of AI in Developing Speaking Skill - Wersi Murtini, Ni Made (Journal on Studies in English Language Teaching (JOSELT), 2025)
This study explored the perceptions of novice university students toward the use of Artificial Intelligence (AI) in developing English speaking skills. This qualitative study aims to investigate how novice learners perceive the role of AI in supporting their English speaking practice. The participants of this study were 10 novice learners of English Education Study Program who were determined by purposive sampling among 22 students who enrolled the Speaking for Informal Interaction Course. The data were collected through semi-structured interviews which were then analyzed by identifying themes related to learners’ perceptions of AI integration in speaking activities. The findings showed that in general the learners had positive view toward the use of AI in enhancing their speaking skills. They reported that AI tools provided opportunities for more frequent speaking practice, immediate feedback on pronunciation, and greater confidence in expressing their ideas. However, there are challenges noted, such as limited interaction quality compared to human communication. Overall, this study indicated that the integration of AI in speaking activities can support novice English learners in improving their speaking competence, confidence and engagement.